Participatory data - Rambaldi, Giacomo (Technical Centre for Agricultural and Rural Cooperation, 2015)
Participatory 3D modelling is a community-based tool that builds on local and indigenous knowledge for a variety of purposes, such as land use planning, watershed management, disaster prevention, communication and advocacy